The Impact of Organizational Communication on Organizational Citizenship Behavior - Hayati, Fitri; Syafira, Syafira; Utami, Nuria Tri; Musthofa, Imam Amir (IKAMAS: Manajemen Pendidikan Islam, 2023)
This study aims to determine the relationship between organizational commitment and the behavior of organizational members. Correlation and standardized mean values have been carried out to reveal the effect of organizational communication on organizational citizenship behavior . Employee participation is critical to organizational effectiveness. In this case, the employee in question is an employee who is not only reliable, but also has loyalty and commitment, as well as readiness to provide more performance for the organization, or commonly referred to as behavior. The type of research used is descriptive qualitative, with a phenomenological approach to interpreting phenomena . occurs where the researcher is as an instrument, sampling data sources is done by data collection techniques in the form of interviews . Analysis using descriptive analysis and inferential analysis . The results of the descriptive analysis show that in this study, in the organizational circles communication dimension, only the communication dimension with managers is significantly correlated dimensions of altruism and civic virtue of organizational citizen behavior